(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Offshore production separators often experience performance degradation due to suboptimal internal geometry, which promotes flow short-circuiting, high turbulence, and reduced phase separation efficiency. This study uses ANSYS Fluent to compare two full-scale horizontal gas-liquid separator configurations under identical steady-state conditions at 160 psia and 52 psia. Model A (simple perforated baffles) and Model B (inlet diverter, coalescer, demister, and outlet baffles) were evaluated via velocity fields, turbulent kinetic energy (TKE), and pressure profiles. At 52 psia, Model A showed maximum velocity of 16.06 m/s and maximum TKE of 5.40 m²/s², while Model B recorded higher localized values (21.15 m/s, 12.30 m²/s²) confined to the demister region—where elevated velocity aids droplet capture rather than impairing separation. At 160 psia, Model B's maximum TKE (1.24 m²/s²) exceeded Model A's (0.70 m²/s²) by 77%, but with uniform cross-sectional flow compared to Model A's concentrated centerline jets. Gas outlet pressure drop across Model B increased from 0.1 psi at high pressure to 0.95 psi at low pressure (versus Model A's 0.2–0.3 psi), representing an acceptable trade-off for improved separation potential. The pressure difference between liquid and gas outlets reached 1.2 psi in Model B at low pressure versus 0.3 psi in Model A. These findings suggest that advanced internals may reduce stagnant zones by approximately 40–50% and localize turbulence, which could improve separation efficiency without disproportionately increasing overall pressure drop. However, direct separation efficiency metrics (e.g., droplet carryover, entrainment fraction) were not simulated and should be addressed in future work. Contribution to Clean Energy: This work supports cleaner offshore production by identifying internal geometries that potentially reduce energy intensity and greenhouse gas emissions. By minimizing turbulence-induced droplet carryover and flow short-circuiting, the proposed design may reduce fuel consumption per barrel of produced fluid and lower flaring from liquid carryover. These efficiency gains demonstrate how retrofitting existing fossil infrastructure could serve as a pragmatic pathway within Africa's just energy transition. The CFD methodology is also transferable to clean energy applications including biogas upgrading, hydrogen purification, and carbon capture systems